Electrolyte film and preparation method thereof
Through the water -based flow -delay method, the spurs and electrolyte thin film solves the problem of pollution and health hazards when preparing ultra -thin electrolyte to prepare ultra -thin electrolytes, realize green environmental protection, low -cost electrolyte preparation, significantly reduced battery ohm resistance, suitable for medium and low temperature SOFC Essence
Patent Information
- Application Number
- CN202411674857.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, when using organic solvents to prepare ultra-thin electrolytes, there are problems of pollution and health hazards.
Use the water -based flow delay method and electrolyte thin film. By dissolving electrolyte raw materials, adhesives, and dispersers in ultra -pure water for ball grinding, the electrolyte slurry is obtained, and then vacuum -off, flowing, and drying. 2 ~ 8 μm electrolyte film.
The preparation of electrolyte filmless film without pollution, green and environmentally friendly, reduced production costs, significantly reduced the battery ohm resistance, and met SOFC use needs under low temperature conditions.
Smart Images

Figure CN119381486A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of fuel cells, and in particular to an electrolyte film and a preparation method thereof. Background Art
[0002] Fuel cell power generation is the fourth generation of power generation technology after hydropower, thermal power and nuclear power. Fuel cells can directly convert the chemical energy of fuel into electrical energy without being limited by the efficiency of the Carnot heat engine. Therefore, they are an efficient and clean energy source and are known as the green energy of the 21st century.
[0003] Among them, Solid Oxide Fuel Cells (SOFC) are considered to be the most promising fuel cell. In SOFC, the main function of the electrolyte is to transfer oxygen ions between the cathode and the anode and to effectively isolate the fuel and the oxidant, which requires the electrolyte to have a sufficiently dense structure and a sufficiently high ionic conductivity at the operating temperature. Generally, an ultra-thin electrolyte with a thickness of 2 to 10 μm is an ideal electrolyte, which can not only satisfy the electrolyte's role as a barrier between the cathode and the anode, but also enable the battery to have satisfactory performance.
[0004] However, in the current methods for preparing ultra-thin electrolytes, the widely used slurry systems are all organic systems or mixed systems. Organic solvents are volatile and toxic, and they will produce waste gas during the production process and cause health hazards to humans.
[0005] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0006] The purpose of the present disclosure is to provide an electrolyte film and a preparation method thereof, aiming to solve the pollution problem caused by using organic solvents to prepare ultra-thin electrolytes.
[0007] Other features and advantages of the present disclosure will become apparent from the following detailed description, or may be learned in part by the practice of the present disclosure.
[0008] According to one aspect of the present disclosure, there is provided a method for preparing an electrolyte film, comprising:
[0009] The electrolyte raw material, the binder and the dispersant are dissolved in ultrapure water and then ball-milled to obtain an electrolyte slurry; wherein the electrolyte raw material is one or more of a ZrO2-based, CeO2-based, Bi2O3-based, and a perovskite-type electrolyte; the binder includes one or more of polyethylene glycol, carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinyl alcohol, polyimide, polyethyleneimine, and alginate; the dispersant includes ethylene glycol and phosphate;
[0010] The electrolyte slurry is subjected to vacuum degassing, and then cast and dried to obtain an electrolyte film, which is used to make a half-cell according to the electrolyte film; the thickness of the electrolyte in the half-cell is 2 to 8 μm.
[0011] Optionally, the mass proportion of the electrolyte raw material is 40% to 60%; the mass proportion of the binder is 10% to 40%; and the mass proportion of the dispersant is 5% to 20%.
[0012] Optionally, the process parameters of the ball milling are: a ball milling speed of 250 to 400 rpm and a ball milling time of 8 to 12 hours.
[0013] Optionally, the viscosity of the electrolyte slurry is 3000-8000 mPa·s.
[0014] Optionally, the process parameters of the casting are: vacuum degassing time is 15 to 40 minutes, the roller rotates at a speed of 0.2 to 0.6 m / min during casting, and the oven temperature of the casting machine is 35 to 60°C.
[0015] Optionally, the drying process parameters are: drying time is 15 to 50 minutes.
[0016] Optionally, the manufacturing of a half-cell based on the electrolyte film includes: laminating the electrolyte film and the anode film under hot isostatic pressing to form a half-cell embryo; wherein the thickness of the electrolyte in the half-cell embryo is 6 to 12 μm; sintering the half-cell embryo according to a preset sintering temperature and sintering time, and obtaining a half-cell after cooling.
[0017] Optionally, the process parameters of the lamination are: pressure of 10 to 30 MPa, temperature of 30 to 50° C., and holding time of 10 to 20 min.
[0018] Optionally, the sintering process parameters are: the sintering crucible is an alumina crucible, the sintering temperature is 1200-1400° C., the holding time is 24-36 hours, and the cooling method is furnace cooling.
[0019] According to a second aspect of the present disclosure, an electrolyte membrane is provided, characterized in that it is obtained by using the preparation method of the electrolyte membrane as described above.
[0020] The exemplary embodiments of the present disclosure may have some or all of the following beneficial effects:
[0021] In the technical solutions provided in some embodiments of the present disclosure, on the one hand, an ultra-thin electrolyte for medium and low temperature fuel cells is prepared by a green and environmentally friendly aqueous electrolyte slurry. Compared with the traditional organic system or composite system, the pure water system is pollution-free, green and environmentally friendly, non-toxic and harmless, reduces production costs, and is friendly to humans; on the other hand, the electrolyte is thin-filmed to prepare a half-cell with an electrolyte thickness of 2 to 8 μm, which can meet the use requirements of SOFC under medium and low temperature conditions and can significantly reduce the battery ohmic resistance; on the other hand, compared with traditional methods with high energy consumption, low yield and cumbersome steps, the electrolyte film preparation method in the present disclosure can improve the production capacity of thin-film electrolytes by using simple steps, and through fine process control, the cost of thin-film electrolytes can be greatly reduced.
[0022] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings herein are incorporated into the specification and constitute a part of the specification, showing embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:
[0024] Figure 1 A schematic diagram schematically shows a process of preparing a method for an electrolyte film in an exemplary embodiment of the present disclosure;
[0025] Figure 2 Schematically showing a SEM photograph of an electrolyte prepared in Example 1 in an exemplary embodiment of the present disclosure;
[0026] Figure 3 Schematically showing a SEM photograph of a cross section of a half-cell prepared in Example 1 of the exemplary embodiment of the present disclosure;
[0027] Figure 4 Schematically showing a SEM photograph of an electrolyte prepared in Example 2 in an exemplary embodiment of the present disclosure;
[0028] Figure 5 Schematically showing a SEM photograph of a cross section of a half-cell prepared in Example 2 of the exemplary embodiment of the present disclosure;
[0029] Figure 6The EIS impedance spectrum of a half-cell prepared in Example 3 in the exemplary embodiment of the present disclosure is schematically shown. DETAILED DESCRIPTION
[0030] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that this disclosure will be more comprehensive and complete and will fully convey the concept of the example embodiments to those skilled in the art.
[0031] In addition, the described features, structures or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced without one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known methods, devices, implementations or operations are not shown or described in detail to avoid blurring the various aspects of the present disclosure.
[0032] The block diagrams shown in the accompanying drawings are merely functional entities and do not necessarily correspond to physically independent entities. That is, these functional entities may be implemented in software form, or in one or more hardware modules or integrated circuits, or in different networks and / or processor devices and / or microcontroller devices.
[0033] The flowcharts shown in the accompanying drawings are only exemplary and do not necessarily include all the contents and operations / steps, nor must they be executed in the order described. For example, some operations / steps can be decomposed, and some operations / steps can be combined or partially combined, so the actual execution order may change according to actual conditions.
[0034] Fuel cell power generation is the fourth generation of power generation technology after hydropower, thermal power and nuclear power. It is an energy conversion device that is fundamentally different from traditional methods. Fuel cells can directly convert the chemical energy of fuel into electrical energy without being limited by the efficiency of the Carnot heat engine. Therefore, they are an efficient and clean energy source and are known as the green energy of the 21st century. In today's world, the increasingly serious energy crisis and environmental pollution make the development of fuel cell technology more significant.
[0035] Among them, Solid Oxide Fuel Cells (SOFC) are considered to be the most promising fuel cell, which has the following advantages: First, it is all solid, without problems such as liquid electrode corrosion and electrolyte leakage, and the electrolyte maintenance and operation costs are low and safe; second, it has a wide range of uses and can be used as both a fixed power source (small power station) and a small mobile power source; third, it has strong fuel adaptability. The adaptability of SOFC to fuel is unmatched by other types of fuel cells. It can use pure hydrogen as fuel, as well as natural gas, city gas, biomass gas, methanol, gasoline, diesel and other light hydrocarbons as fuel; fourth, it operates at high temperatures (700-800°C), does not require precious metal catalysts, and saves costs.
[0036] However, traditional high-temperature SOFC has problems in both materials and system design. Therefore, medium and low temperature is the only way for SOFC to develop. Medium and low temperature fuel cells not only basically maintain the characteristics of high-temperature batteries, but also have many new advantages, such as: low operating temperature (<700℃); easy to seal; reduced interlayer diffusion, extended battery life; cheap stainless steel can be used as a connecting material. The development of medium and low temperature SOFC is not aimed at reducing energy output. On the contrary, high-performance battery technology is the goal pursued by people. Therefore, reducing the internal resistance and polarization of fuel cells is the focus of SOFC medium and low temperature process research. At present, the two most effective methods for medium and low temperature are: one is electrolyte filmization; the other is the development of new materials: including cathode, electrolyte, etc. In SOFC, the main function of the electrolyte is to transfer oxygen ions between the cathode and anode and to effectively isolate the fuel and oxidant. This requires the electrolyte to have a sufficiently dense structure and a sufficiently high ionic conductivity at the operating temperature. Generally, an ultra-thin electrolyte with a thickness of 2 to 10 μm is an ideal electrolyte, which can not only meet the electrolyte as a barrier between the cathode and the anode but also make the battery have satisfactory performance.
[0037] At present, the preparation of ultra-thin electrolytes mainly includes the following methods: tape casting, screen printing, electrochemical vapor deposition, magnetron sputtering and thermal spraying. Except for tape casting, the production cost of other methods is relatively high and not suitable for large-scale production; therefore, tape casting is the current mainstream method, which is simple to operate, stable in process, can achieve continuous batch production, and has low cost. However, the widely used slurry systems are all organic systems or mixed systems. Organic solvents are volatile and toxic, and waste gas will be generated during the production process and cause health hazards to people, which does not meet the concept of green production and sustainable development.
[0038] Therefore, in view of the defects in the existing technology, the use of a simple, efficient and low-cost method to prepare an electrolyte for SOFC with an ultra-thin structure is an effective way to solve the industrialization of high-performance SOFC. Therefore, replacing organic solvents with environmentally friendly solvents is an imperative sustainable development policy. Water is an environmentally friendly solvent that does not produce waste gas and pollution, which is in line with the concept of green and environmentally friendly production.
[0039] Therefore, the present invention provides a method for preparing ultra-thin electrolytes for medium and low temperature fuel cells by water-based tape casting. The preparation process has the advantages of simple steps, green environmental protection, and low cost. The electrolyte can greatly reduce the ohmic resistance, meet the use requirements of SOFC under medium and low temperature conditions, and improve the output power of the battery.
[0040] The implementation details of the technical solution of the embodiment of the present disclosure are elaborated in detail below.
[0041] Figure 1 The schematic diagram of the process of preparing a method of an electrolyte film in an exemplary embodiment of the present disclosure is schematically shown. Figure 1 As shown, the method for preparing the electrolyte film includes step S101 and step S103:
[0042] Step S101, dissolving electrolyte raw materials, binders and dispersants in ultrapure water and then ball milling to obtain electrolyte slurry; wherein the electrolyte raw materials are one or more of ZrO2-based, CeO2-based, Bi2O3-based, and perovskite-type electrolytes; the binders include one or more of polyethylene glycol, carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinyl alcohol, polyimide, polyethyleneimine, and alginate; the dispersants include ethylene glycol and phosphate;
[0043] Step S103, vacuum degassing the electrolyte slurry, casting and drying to obtain an electrolyte film for making a half-cell according to the electrolyte film; wherein the thickness of the electrolyte in the half-cell is 2-8 μm.
[0044] In the technical solutions provided in some embodiments of the present disclosure, on the one hand, an ultra-thin electrolyte for medium and low temperature fuel cells is prepared by a green and environmentally friendly aqueous electrolyte slurry. Compared with the traditional organic system or composite system, the pure water system is pollution-free, green and environmentally friendly, non-toxic and harmless, reduces production costs, and is friendly to humans; on the other hand, the electrolyte is thin-filmed to prepare a half-cell with an electrolyte thickness of 2 to 8 μm, which can meet the use requirements of SOFC under medium and low temperature conditions and can significantly reduce the battery ohmic resistance; on the other hand, compared with traditional methods with high energy consumption, low yield and cumbersome steps, the electrolyte film preparation method in the present disclosure can improve the production capacity of thin-film electrolytes by using simple steps, and through fine process control, the cost of thin-film electrolytes can be greatly reduced.
[0045] Hereinafter, each step of the method for preparing the electrolyte membrane in this exemplary embodiment will be described in more detail with reference to the accompanying drawings and examples.
[0046] In step S101 , electrolyte raw materials, a binder and a dispersant are dissolved in ultrapure water and then ball-milled to obtain electrolyte slurry.
[0047] Specifically, a certain proportion of electrolyte raw materials, binders, and dispersants are weighed and dissolved in ultrapure water, and mechanically mixed in a ball mill at a certain speed, and after a period of time, a uniformly mixed electrolyte slurry with a certain viscosity is obtained.
[0048] The electrolyte raw material is one or more of ZrO2-based, CeO2-based, Bi2O3-based, and perovskite-type electrolytes; the binder includes polyethylene glycol (PEG, M n =2000-10000), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyimide (PI), polyethyleneimine (PEI) and alginate (ALG) or more; the dispersant includes ethylene glycol and phosphate.
[0049] In one embodiment of the present disclosure, the mass proportion of the electrolyte raw material is 40% to 60%; the mass proportion of the binder is 10% to 40%; and the mass proportion of the dispersant is 5% to 20%.
[0050] In one embodiment of the present disclosure, the process parameters of the ball milling are: the ball milling speed is 250-400 rpm, and the ball milling time is 8-12 hours.
[0051] In one embodiment of the present disclosure, the viscosity of the electrolyte slurry is 3000-8000 mPa·s.
[0052] In step S103, the electrolyte slurry is subjected to vacuum degassing treatment, and then cast and dried to obtain an electrolyte film, which is used to manufacture a half-cell according to the electrolyte film.
[0053] Specifically, the electrolyte slurry obtained in step S101 is subjected to vacuum degassing treatment for a certain period of time, and is tape-cast on a tape-casting machine using certain process parameters. After drying and curing, an electrolyte film with uniform thickness, smooth surface and uniform texture can be obtained.
[0054] In one embodiment of the present disclosure, the process parameters of the casting are: vacuum degassing time is 15 to 40 minutes, the roller rotates at a speed of 0.2 to 0.6 m / min during casting, and the oven temperature of the casting machine is 35 to 60°C.
[0055] In one embodiment of the present disclosure, the drying process parameters are: drying time is 15 to 50 minutes.
[0056] In one embodiment of the present disclosure, the manufacturing of a half-cell based on the electrolyte film includes: laminating the electrolyte film and the anode film under hot isostatic pressing to form a half-cell embryo; wherein the thickness of the electrolyte in the half-cell embryo is 6 to 12 μm; sintering the half-cell embryo according to a preset sintering temperature and sintering time, and obtaining a half-cell after cooling.
[0057] Specifically, the electrolyte film is cut into a certain size, and the cut electrolyte film and the anode film are laminated into a half-cell embryo using a laminating machine at a certain temperature and pressure under hot isostatic pressing.
[0058] In one embodiment of the present disclosure, the process parameters of the lamination are: pressure of 10-30 MPa, temperature of 30-50° C., and holding time of 10-20 min.
[0059] In one embodiment of the present disclosure, the sintering process parameters are: the sintering crucible is an alumina crucible, the sintering temperature is 1200-1400°C, the holding time is 24-36 hours, and the cooling method is furnace cooling. The thickness of the electrolyte of the key material inside the half-cell after sintering ranges from 2 to 8 μm.
[0060] Example 1
[0061] This embodiment includes the following steps:
[0062] (1) Slurry preparation: Weigh 50% by mass of electrolyte raw material 3YSZ and 10% by mass of binder polyethylene glycol (PEG, M n =2000) and polyacrylic acid (PAA) compound binder, 5% by mass of ethylene glycol as dispersant, dissolved in ultrapure water, the ball mill speed is set to 250rmp / min, the ball milling time is 8h, and the viscosity of the electrolyte slurry obtained after ball milling is 3000mPa·s.
[0063] (2) Tape casting: The electrolyte slurry obtained in step (1) was subjected to vacuum degassing for 15 min, and then cast after degassing. The roller rotated at a speed of 0.2 m / min, and the oven temperature of the tape casting machine was set to 35°C. After drying for 15 min and curing, the green embryo of the electrolyte film obtained had a thickness of 6 μm.
[0064] (3) Lamination: The electrolyte green sheets and the anode green sheets are laminated by hot isostatic pressing at a pressure of 10 MPa, a temperature of 30° C., and a holding time of 10 minutes.
[0065] (5) Sintering: The stacked half-cell is sintered in an alumina crucible at a sintering temperature of 1200°C for 24 hours. The temperature is cooled by the furnace. The thickness of the electrolyte inside the sintered half-cell is 2 μm.
[0066] Figure 2 The SEM image of an electrolyte prepared in Example 1 of the exemplary embodiment of the present disclosure is schematically shown. Figure 2 As shown, the prepared electrolyte is very dense, the grains are closely arranged, and there are no obvious holes or large cracks, indicating that the electrolyte prepared by the method of this embodiment has a dense structure.
[0067] Figure 3 The SEM photograph of the cross section of a half-cell prepared in Example 1 of the exemplary embodiment of the present disclosure is schematically shown. Figure 3 As shown, it can be seen that the electrolyte (the area marked by the white arrow) is tightly attached to the internal functional layer of the anode, with no obvious cracks or places where the layers do not fit together. After measurement, its thickness is only 2μm, which meets the thickness requirements for electrolyte film.
[0068] Example 2
[0069] This embodiment includes the following steps:
[0070] (1) Slurry preparation: Weigh 55% by mass of electrolyte raw material 3YSZ and 25% by mass of binder PEG (M n =10000) and PVA compound binder, 10% by mass of dispersant phosphate, dissolved in ultrapure water, the ball mill speed is set to 300 rpm / min, the ball milling time is 9.5 h, and the viscosity of the electrolyte slurry obtained after ball milling is 5500 mPa·s.
[0071] (2) Tape casting: The electrolyte slurry obtained in step (1) was subjected to vacuum degassing for 20 min, and then cast after degassing. The roller rotated at a speed of 0.5 m / min, and the oven temperature of the tape casting machine was set to 40°C. After drying for 35 min and curing, the green embryo of the electrolyte film obtained had a thickness of 11 μm.
[0072] (3) Lamination: The electrolyte green sheets and the anode green sheets are laminated by hot isostatic pressing at a pressure of 15 MPa, a temperature of 30°C, and a holding time of 10 minutes.
[0073] (5) Sintering: The stacked half-cell is sintered in an alumina crucible at a sintering temperature of 1320°C for 32 hours. The cooling method is furnace cooling. The electrolyte thickness of the sintered half-cell is 8 μm.
[0074] Figure 4The SEM photo of an electrolyte prepared in Example 2 of the exemplary embodiment of the present disclosure is schematically shown. Figure 4 As shown, it can be seen that the prepared electrolyte is very dense, the grains are closely arranged, and there are no obvious holes or large cracks in the body and grain boundaries, indicating that the electrolyte prepared by the method of this embodiment has a dense structure.
[0075] Figure 5 The SEM photo of the cross section of a half-cell prepared in Example 2 of the exemplary embodiment of the present disclosure is schematically shown. Figure 5 As shown, it can be seen that the electrolyte (the area marked by the white arrow) is closely attached to the internal functional layer of the anode, without obvious cracks or places where the layers do not fit together. After measurement, its thickness is about 8μm, which meets the thickness requirements for electrolyte film.
[0076] Example 3
[0077] This embodiment includes the following steps:
[0078] (1) Slurry preparation: Weigh 45% of the electrolyte raw material BZCY, 30% of the binder mass fraction of SBR and PAA composite binder, and 10% of the dispersant ethylene glycol, and dissolve them in ultrapure water. Set the ball mill speed to 350 rpm and the ball milling time to 10 h. The viscosity of the electrolyte slurry obtained after ball milling is 6000 mPa·s.
[0079] (2) Tape casting: The electrolyte slurry obtained in step (1) was subjected to vacuum degassing for 30 min, and then cast after degassing. The roller rotated at a speed of 0.4 m / min, and the oven temperature of the tape casting machine was set to 45°C. After drying for 30 min and curing, the green embryo of the electrolyte film obtained had a thickness of 12 μm.
[0080] (3) Lamination: The electrolyte green sheets and the anode green sheets are laminated by hot isostatic pressing at a pressure of 20 MPa, a temperature of 35°C, and a holding time of 10 minutes.
[0081] (5) Sintering: The stacked half-cell is sintered in an alumina crucible at a sintering temperature of 1280°C for 28 hours. The cooling method is furnace cooling. The electrolyte thickness of the sintered half-cell is 8 μm.
[0082] Figure 6 The EIS impedance spectrum of a half-cell prepared in Example 3 of the exemplary embodiment of the present disclosure is schematically shown. The test temperature of the EIS performance is 650°C, which meets the low temperature trial temperature of SOFC. Figure 6The EIS impedance spectrum, where the horizontal axis represents the real resistance of the single cell and the vertical axis represents the imaginary resistance of the single cell, shows that the ohmic resistance of the single cell is 0.043Ωcm 2 The ohmic resistance is low, which shows that the thin film electrolyte can reduce the ohmic resistance of the battery, and further shows that the electrolyte and the anode are tightly bonded and well matched.
[0083] Example 4
[0084] This embodiment includes the following steps:
[0085] (1) Slurry preparation: Weigh 60% by mass of the electrolyte raw material SDC, 40% by mass of the binder CMC, PVA and PEI compound, and 20% by mass of the dispersant ethylene glycol and phosphate, dissolve them in ultrapure water, set the ball mill speed to 400 rpm, and the ball milling time to 12 h. The viscosity of the electrolyte slurry obtained after ball milling is 8000 mPa·s.
[0086] (2) Tape casting: The electrolyte slurry obtained in step (1) is subjected to vacuum degassing for 40 min, and then cast after degassing. The roller rotates at a speed of 0.6 m / min, and the oven temperature of the tape casting machine is set to 60°C. After drying for 50 min and curing, the green electrolyte film has a thickness of 10 μm.
[0087] (3) Lamination: The electrolyte green sheets and the anode green sheets are laminated by hot isostatic pressing at a pressure of 30 MPa, a temperature of 50°C, and a holding time of 20 minutes.
[0088] (5) Sintering: The stacked half-cell is sintered in an alumina crucible at a sintering temperature of 1350°C for 30 hours. The cooling method is furnace cooling. The electrolyte thickness inside the sintered half-cell is 6 μm.
[0089] The above embodiments are only used to specifically illustrate the implementation process of the present invention and do not limit the actual protection scope of the present invention. Professionals in this field need to understand that any improvements and equivalent changes made to the present invention are in line with the content and innovative spirit of the present invention and should fall within the scope of patent protection covered by the present invention.
[0090] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. The present disclosure is intended to cover any variations, uses or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure.
[0091] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A method for preparing an electrolyte film, characterized in that: include: The electrolyte raw material, the binder and the dispersant are dissolved in ultrapure water and then ball-milled to obtain an electrolyte slurry; wherein the electrolyte raw material is one or more of a ZrO2-based, CeO2-based, Bi2O3-based, and a perovskite-type electrolyte; the binder includes one or more of polyethylene glycol, carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinyl alcohol, polyimide, polyethyleneimine, and alginate; the dispersant includes ethylene glycol and phosphate; The electrolyte slurry is subjected to vacuum degassing, and then cast and dried to obtain an electrolyte film, which is used to make a half-cell according to the electrolyte film; wherein the thickness of the electrolyte in the half-cell is 2 to 8 μm.
2. The method for preparing an electrolyte film according to claim 1, characterized in that: The mass proportion of the electrolyte raw material is 40% to 60%; the mass proportion of the binder is 10% to 40%; and the mass proportion of the dispersant is 5% to 20%.
3. The method for preparing an electrolyte membrane according to claim 1, characterized in that: The process parameters of the ball milling are: a ball milling speed of 250 to 400 rpm and a ball milling time of 8 to 12 hours.
4. The method for preparing an electrolyte film according to claim 1, characterized in that: The viscosity of the electrolyte slurry is 3000-8000 mPa·s.
5. The method for preparing an electrolyte membrane according to claim 1, characterized in that: The process parameters of the casting are as follows: vacuum degassing time is 15 to 40 minutes, the roller rotates at a speed of 0.2 to 0.6 m / min during casting, and the oven temperature of the casting machine is 35 to 60°C.
6. The method for preparing an electrolyte membrane according to claim 1, characterized in that: The drying process parameters are as follows: drying time is 15 to 50 minutes.
7. The method for preparing an electrolyte membrane according to claim 1, characterized in that: The method of manufacturing a half-cell according to the electrolyte film comprises: The electrolyte film and the anode film are laminated under hot isostatic pressing to form a half-cell embryo; wherein the thickness of the electrolyte in the half-cell embryo is 6 to 12 μm; The half-cell green body is sintered according to a preset sintering temperature and sintering time, and a half-cell is obtained after cooling.
8. The method for preparing an electrolyte membrane according to claim 1, characterized in that: The process parameters of the lamination are: pressure of 10-30 MPa, temperature of 30-50° C., and pressure holding time of 10-20 min.
9. The method for preparing an electrolyte membrane according to claim 1, characterized in that: The process parameters of the sintering are as follows: the sintering crucible is an alumina crucible, the sintering temperature is 1200-1400° C., the heat preservation time is 24-36 hours, and the cooling method is furnace cooling.
10. An electrolyte membrane, characterized in that: The electrolyte film is obtained by using the method for preparing the electrolyte film according to claims 1 to 9 above.